Training of Residents in Cardiac Surgery—Does It Have Impact on the Outcome? - Szczechowicz, Marcin Piotr; Easo, Jerry; Zhigalov, Konstantin; Mashhour, Ahmed; Mkalaluh, Sabreen; Weymann, Alexander (The Thoracic and Cardiovascular Surgeon, 2019)
Objectives In many centers, training in cardiac surgery is considered to increase perioperative risk. This study aims to test whether a resident working as the main operator is a genuine risk factor.Methods We analyzed patients who underwent elective isolated aortic valve replacement, elective isolated coronary artery bypass grafting, or both, in our institution, from 2008 to 2016. Redo- and off-pump surgery, ejection fraction < 30%, and other concomitant procedures were the exclusion criteria. After this selection, we included 3,077 patients in our study. Within this group, 357 (11.6%) had been operated by residents and 2,720 (88.4%) by senior surgeons. We performed propensity score matching using the nearest neighbor method with a ratio of 1:2, considering the most important preoperative conditions. In this way, the 357 patients operated by residents were matched with the 714 patients who were operated by senior surgeons. The standardized mean differences were highly reduced after matching, so both groups had similar risk profiles. We compared surgical data, postoperative adverse events, and the 30-day mortality between the two groups.Results The times of surgery, cardiopulmonary bypass, and cross-clamp were longer if residents operated (p < 0.001). There were no differences regarding postoperative adverse events, time of mechanical ventilation, and the intensive care unit length of stay. The 30-day mortality rates of the two groups were very similar (p = 0.75, power = 0.8).Conclusion Training in cardiac surgery is safe, and carefully selected patients can be operated by residents without increased risk of perioperative mortality and complications.
Keywords: cardiac; heart valve surgery; coronary artery bypass grafting; CABG education, all levels